Effect of Copayment on Dental Visits: A Regression Discontinuity Analysis. (November 2020) - Cooray, U.; Aida, J.; Watt, R.G.; Tsakos, G.; Heilmann, A.; Kato, H.; Kiuchi, S.; Kondo, K.; Osaka, K.
Despite their prevalence and burdens, oral diseases are neglected in universal health coverage. In Japan, a 30% copayment (out of pocket) by the user and a 70% contribution by Japan's universal health insurance (JUHI) are required for dental and medical services. From the age of 70 y, an additional 10% is offered by JUHI (copayment, 20%; JUHI, 80%). This study aimed to investigate the effect of cost on dental service use among older adults under the current JUHI system. A regression discontinuity quasi-experimental method was used to investigate the causal effect of the JUHI discount policy on dental visits based on cross-sectional data. Data were derived from the 2016 Japan Gerontological Evaluation Study. This analysis contained 7, 161 participants who used JUHI, were aged 68 to 73 y, and responded to questions regarding past dental visits. Analyses were controlled for age, sex, number of teeth, and equalized household income. Mean ± SD age was 72.1 ± 0.79 y for the discount-eligible group and 68.9 ± 0.78 y for the noneligible group. During the past 12 mo, significantly more discount-eligible participants had visited dental services than noneligible participants (66.0% vs. 62.1% for treatment visits, 57.7% vs. 53.1% for checkups). After controlling for covariates, the effect of discount eligibility was significant on dental treatment visits (odds ratio [OR], 1.36; 95% CI, 1.32 to 1.40) and dental checkups (OR, 1.49; 95% CI, 1.44 to 1.54) in the regression discontinuity analysis. Similar findings were observed in triangular kernel-weighted models (OR, 1.38 [95% CI, 1.34 to 1.44]; OR, 1.52 [95% CI, 1.47 to 1.56], respectively). JUHI copayment discount policy increases oral health service utilization among older Japanese. The price elasticity for dental checkup visits appears to be higher than for dental treatment visits. Hence, reforming the universal health coverage system to improve the affordability of relatively inexpensive preventive care could increase dental service utilization in Japan.